(untitled) (Scientific journal of the Fergana State University, 2024)
From an agricultural point of view, fertilizer should be applied in such a way that it allows to increase the cotton yield, and the resulting additional crop covers all the costs associated with the application of fertilizers. The rate of potassium fertilization with phosphorus is determined depending on the amount of mobile phosphorus in the soil and the amount of exchangeable potassium. This ratio of phosphorus and potassium increases by 10% in marginal soils and decreases by 10% in fertile soils. The above calculations for fertilizers are not yet perfect. However, other methods of calculating the fertilizer rate cannot fully satisfy the basic requirements for maximum additional crop production if less fertilizer is used per unit of crop. But the important thing is that every kilogram of nitrogen given to cotton yields at least 14-15 kg of cotton.